Mini review: Naegleria fowleri the fatal meningoencephalitis - Nuha Jaboori Hadi (University of Thi-Qar Journal of Science, 2022)
Primary amoebic meningoencephalitis (PAM) is a fatal parasitic disease caused by a free-living amoeba called Naegleria fowleri also called a brain-eating amoeba. The parasite can invade the central nervous system causing brain damage and death in a few days. PAM is characterized by a high fatal mortality rate of 98% and the estimated time for death is less than two weeks after symptoms onset making it the most deadly parasitic infection in the world. Treatment options for PAM are still the major obstacle since the drugs cannot pass the blood-brain barrier (BBB) to kill the parasite leading to a high mortality rate. This review came to focus on the new approach and updating regarding the new treatment options and recent case reports in addition to elucidating the diagnosis process.